2020
DOI: 10.25082/ahb.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Social prescribing as an intervention for people with work-related injuries and psychosocial difficulties in Australia

Abstract: Psychosocial interventions that encourage optimism and connectedness can promote workplace injury recovery and improve wellbeing. A mixed-methods evaluation of a twelve-week program for injured workers in Sydney, Australia, explored three research questions: if a social prescribing approach contributed to (1) increased social and economic participation, (2) improved psychological functioning and quality of life, and (3) decreased health service utilisation. Retrospective analysis of pre-and post-intervention d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 22 publications
0
28
0
7
Order By: Relevance
“…Green prescribing builds on the earlier concept of prescribing exercise and diet-based interventions [27]-a variant that was pioneered by general practitioners (GPs) in New Zealand in the 1990s [28]. It also builds on the recent social prescribing movement, which can be defined as: "a way of linking patients in primary care with sources of support within the community-usually provided by the voluntary and community sector, offering GPs a non-medical referral option that can operate alongside existing treatments to improve health and well-being", [29] (p. 7) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Green prescribing builds on the earlier concept of prescribing exercise and diet-based interventions [27]-a variant that was pioneered by general practitioners (GPs) in New Zealand in the 1990s [28]. It also builds on the recent social prescribing movement, which can be defined as: "a way of linking patients in primary care with sources of support within the community-usually provided by the voluntary and community sector, offering GPs a non-medical referral option that can operate alongside existing treatments to improve health and well-being", [29] (p. 7) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The study aims to recruit 140 adults with ongoing mental illness (mood and psychotic disorders), living in the community at the Gold Coast (expected n = 45) and in Sydney (expected n = 95). Participants will be care-coordination clients of PCCS, an NGO that has previously developed and implemented SP programs in Australia [33,34]. PCCS has a steady flow of new care-coordination clients (who are referred by their GP) and these will form the recruitment pool.…”
Section: Participantsmentioning
confidence: 99%
“…However, Australia's first holistic SP programs for individuals with mental illness and disabilities have only been active since 2016, primarily implemented by NGO Primary and Community Services (PCCS) [33,34]. These ongoing programs offer care-coordination and community referral to local public, private, and community-run health and welfare services, in addition to internal and external social activities (e.g., art classes, coffee groups).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-known models of social prescribing include ‘arts on prescription’ [ 16 ], ‘education on prescription’ [ 17 ], and ‘exercise on prescription’ [ 18 ]. A randomised controlled trial [ 19 ], single arm trials [ 20 23 ], and a systematic review [ 24 ] have found that social prescribing programs can be effective in reducing participants’ social isolation and loneliness, increasing community integration, and improving mood and mental well-being. However, there is a large variation in the models of social prescribing and the methods used to evaluate them [ 25 ], and this has led some researchers to be critical of the approach [ 26 ].…”
Section: Introductionmentioning
confidence: 99%